Plants in alcoholic beverages on the Croatian islands, with special reference to rakija travarica - Łukasz Łuczaj; Marija Jug-Dujaković; Katija Dolina; Ivana Vitasović-Kosić (BMC, 2019)
Abstract Background This paper aims to record the species used for flavouring and making alcoholic drinks, mainly rakija, on the islands of the Adriatic (Croatia). Methods Our data comes from 295 interviews performed on 36 islands, in both the Dalmatian and Kvarner areas of the Adriatic. Results Altogether, 114 species are used-46% from wild locations only, 15% both wild and cultivated, 38% only cultivated and two species are imported. The most common local alcohol is wine, made without spices, but grape pomace distillate is often flavoured with single or mixed species. The mix is called travarica. The most commonly used species are Foeniculum vulgare Mill., Myrtus communis L., Salvia officinalis L., Ruta graveolens L., Juniperus oxycedrus L., Ceratonia siliqua L., Juglans regia L., Citrus spp., Ficus carica L., Laurus nobilis L., Rosmarinus officinalis L., Artemisia absinthium L., Rosa centifolia L., Mentha × piperita L. and M. spicata L. Unfortunately, the widespread phenomenon of distilling Arbutus unedo L. fruits and fermenting Juniperus 'wine' is now extinct. Apart from grapes, the only commonly distilled fruit now is Ficus carica. Conclusions It is striking that nearly all the plants are either wild or cultivated locally, which, in addition to the fact that the alcohol is made locally, shows the incredible local culinary self-sufficiency of the area. The number of species used is also very impressive.